2019
DOI: 10.1007/s42452-019-0746-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of LDPE degrading potential Aspergillus species isolated from municipal landfill sites of Agra

Abstract: Polythene bags have become an article of common usage in daily life. Huge accumulation of plastic waste cause severe threat to humans, animals and our environment. Recently microbes have become the focus of interest for environment friendly disposal of plastic waste. In present study 18 different types of fungal species were isolated from soil and two fungal species were screened by using polythene powder. The fungal identification was carried out by genomic DNA isolation followed by PCR and ITS rRNA sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Though weight loss was high in these cases, it takes nearly 90 days whereas C. sphaerospermum used in this study showed weight loss in a week time. The weight loss in LDPE films treated with C. sphaerospermum might be due to consumption of LDPE as a carbon source which is in accordance with previous reports 1 , 36 . The reduction rate (k) of LDPE by C. sphaerospermum was found to be 0.0224/day and the half-life (t 1/2 ) was 30.93 days.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Though weight loss was high in these cases, it takes nearly 90 days whereas C. sphaerospermum used in this study showed weight loss in a week time. The weight loss in LDPE films treated with C. sphaerospermum might be due to consumption of LDPE as a carbon source which is in accordance with previous reports 1 , 36 . The reduction rate (k) of LDPE by C. sphaerospermum was found to be 0.0224/day and the half-life (t 1/2 ) was 30.93 days.…”
Section: Resultssupporting
confidence: 92%
“…This result is in accordance with previous reports of LDPE degradation by Aspergillus sp. 1 , 19 . It has been reported that fungal penetration resulted in physical weakening and disintegration of LDPE strip 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These grew on low density polyethylene (LDPE) causing deformations and reducing the weight and tensile strength of the polymer. Other Aspergillus species isolated from landfills include Aspergillus clavatus (Gajendiran et al, 2016), Aspergillus flavus and Aspergillus terreus (Verma and Gupta, 2019) and with, these were also shown to degrade PE. Fusarium oxysporum, Fusarium falciforme and Purpureocillum lilacinum isolated from an abandoned dumpsite in Northern Italy, showed to cause changes in the PE film morphology (Spina et al, 2021).…”
Section: Conventional Plastic Polymer Degradation By Fungimentioning
confidence: 99%